The effect of a solvent on cellular response to PCL/gelatin and PCL/collagen electrospun nanofibres. (July 2018) - Dulnik, Judyta; Kołbuk, Dorota; Denis, Piotr; Sajkiewicz, Paweł
Graphical abstract: Highlights: Molecular conformations of polypeptides molecules depend on the strength of solvent used. Polypeptides conformation determines exposition of RGD sequence and cellular activity. Although both subjected to denaturation, collagen retains more native structure compared to gelatin. Comparing HFIP and acidic solvents is like win-win situation – depends on the point of view. Abstract: Bicomponent polycaprolactone/gelatin and polycaprolactone/collagen fibres were formed by electrospinning using two kinds of solvents: a representative of commonly used solvents with this polymer composition, highly toxic hexafluoroisopropanol (HFIP) and alternative, less harmful one, the mixture of acetic (AA) and formic (FA) acids. Both material types were subjected to investigations of structure and in-vitro cellular activity. Viscosity and Fourier transform infrared spectroscopy (FTIR) measurements shown that the type of solvent used influences the structure of solution and conformation of polymer molecules. In-vitro quantitative tests as well as cell culture morphology observations proved that materials electrospun with the use of 'green' solvents can yield similar results to those obtained by made with toxic ones. Slightly better cellular response to materials electrospun from HFIP can be explained by relatively well dispersed components within the fibre and more expanded conformation of molecules, resulting in better exposition of RGD (Arg-Gly-Asp) binding sites to cells' integrin receptors.